Tinjauan Perkawinan Wanita Hamil Menurut Khi Di Indonesia - Shinwanudin, M.; Zuhriyyah, Lailatuz (JAS MERAH: Jurnal Hukum dan Ahwal al-Syakhsiyyah, 2021)
Pregnant marriage is marrying a woman who is pregnant out of wedlock, either married by a man who impregnates her or by a man who does not impregnate her. The Marriage Law only implicitly regulates the marriage of pregnant women, namely in Article 2 paragraph (1). While the KHI argues that the law is legal to marry a pregnant woman due to adultery if the man who married her is the man who impregnated her. However, if the woman who marries the woman is not the man who impregnated her, then the law is invalid. This is stated in chapter VIII on pregnant marriage, article 53 KHI.Regarding the lineage of children born from such marriages, KHI gives the view that a legitimate child is a child born from a legal marriage, even though the marriage contract is carried out in a condition where the woman is pregnant out of wedlock (either because of adultery or rape) as long as the man who marries her is the man who got her pregnant.